PENGARUH BI RATE NILAI TUKAR DAN INFLASI TERHADAP PENDAPATAN BAGI HASIL BANK MEGA SYARIAH INDONESIA PERIODE 2019-2023 - Afilatul Agustini; Zaid Raya Argantara (AL-MUJADDID - JURNAL EKONOMI DAN BISNIS ISLAM, 2025)
Indonesia's economy faced many challenges from 2019 to 2023, including the effects of the COVID-19 pandemic, exchange rate fluctuations, and unstable inflation rates. If the BI Rate is lower, it can increase profit margins, while if BI Rate is higher, it can reduce profit margins, Fluctuating exchange rates can affect the operational costs of Islamic banks, if the Rupiah weakens, income from financing in foreign exchange will increase when converted to Rupiah. On the other hand, if the rupiah strengthens, income from financing in foreign currency will decrease when converted to rupiah. High inflation tends to reduce customer purchasing power, which can have a negative impact on profit-sharing income. The formulation of the problem of this study is: 1). Does the BI rate affect Bank Mega Syariah Indonesia's profit-sharing income in the 2019-2023 period? 2). Does the Rupiah exchange rate affect Bank Mega Syariah Indonesia's profit-sharing income in the 2029-2023 period? 3). Does inflation affect Bank Mega Indonesia's profit-sharing income in the 2019-2023 period? 4). Do BI Rate, Rupiah Exchange Rate and Inflation affect Bank Mega Syariah Indonesia's profit-sharing income for the 2019-2023 period? The method used in this study is associative quantitative research. The object of this research is the quarterly bank financial statements of Bank Mega Syariah Indonesia for the 2019-2023 period. The data collection technique uses documentation, data analysis uses multiple linear analysis tests. The result of this study is that the Bi Rate has no effect on Bank Mega Syariah Indonesia's profit-sharing income for the 2019-2023 period, this can be seen from the significance value of 0.078 > 0.05. The exchange rate has no effect on Bank Mega Syariah Indonesia's profit-sharing income for the 2019-2023 period, this can be seen from the significance value of 0.716 > 0.05. Inflation affects Bank Mega Syariah Indonesia's profit-sharing income for the 2019-2023 period this can be seen from a significance value of 0.036 < 0.05. BI Rate, Exchange Rate, and Inflation affect Bank Mega Syariah Indonesia's profit-sharing income for the 2019-2023 period, this can be seen from the significance value of 0.008 < 0.05.